A transcriptome analysis of Benincasa hispida revealed the pathways and genes involved in response to Phytophthora melonis infection - Cai, Jinsen; Yang, Songguang; Liu, Wenrui; Yan, Jinqiang; Jiang, Biao; Xie, Dasen (Frontiers in Plant Science, 2022)
Wilt disease caused by Phytophthora melonis infection is one of the most serious threats to Benincasa hispida production. However, the mechanism of the response of B. hispida to a P. melonis infection remains largely unknown. In the present study, two B. hispida cultivars with different degrees of resistance to P. melonis were identified: B488 (a moderately resistant cultivar) and B214 (a moderately susceptible cultivar). RNA-seq was performed on P. melonis-infected B488 and B214 12 hours post infection (hpi). Compared with the control, 680 and 988 DEGs were respectively detected in B488 and B214. A KEGG pathway analysis combined with a cluster analysis revealed that phenylpropanoid biosynthesis, plant-pathogen interaction, the MAPK signaling pathway-plant, and plant hormone signal transduction were the most relevant pathways during the response of both B488 and B214 to P. melonis infection, as well as the differentially expressed genes in the two cultivars. In addition, a cluster analysis of transcription factor genes in DEGs identified four genes upregulated in B488 but not in B214 at 6 hpi and 12 hpi, which was confirmed by qRT-PCR. These were candidate genes for elucidating the mechanism of the B. hispida response to P. melonis infection and laying the foundation for the improvement of B. hispida.